(S)TEM-EELS as an advanced characterization technique for lithium-ion batteries. (28th April 2021) - Yu, Lei; Li, Matthew; Wen, Jianguo; Amine, Khalil; Lu, Jun
Abstract : (Scanning) transmission electron microscopy–electron energy loss spectroscopy is used as an advanced nano-scale characterization method to clarify the ion diffusion, charge transfer and structure change occurring in lithium-ion batteries. Abstract : Although the lithium-ion battery (LIB) has acquired commercial success as a sustainable power source, it still suffers from multiple challenges for the future applications. In order to further develop next-generation batteries, the dynamics of structure change, charge transfer, and ion diffusion occurring inside the battery need to be deeply understood by advanced characterization techniques. (Scanning) transmission electron microscopy-electron energy loss spectroscopy ((S)TEM-EELS) is an effective method for the nano-scale detection of structural and chemical information in materials. This review systematically introduces the advantages and fundamentals of (S)TEM-EELS and its unique applications in LIBs.